DISTRIBUSI FREKUENSI FAKTOR PENYEBAB PERILAKU HIDUP SEHAT DAN BERSIH MASYARAKAT DI LOKASI CAR FREE DAY KOTA MAKASSAR - Risma Haris; Badriani Badawi; Sartika S; Marlina Marlina; Lutfi Lutfi; Gazali Gazali (UNM Environmental Journals, 2022)
Healthy and Clean Living is important for the community. The purpose of this study was to determine the factors that cause a healthy and clean life for the community at the Car Free Day location in Makassar City. The type of research used in this research is a descriptive approach, namely collecting data to describe the factors that cause healthy and clean living in the community at the Car Free Day location in Makassar City. Based on the results of research that has been conducted from 210 respondents, it can be concluded that the factors causing healthy and clean living behavior in the Car Free Day activity on Jalan Sudirman Makassar City for the female gender indicator are 160 people (76%) who participate, based on age, namely 30- 73 people (35%) are 38 years old and 105 people (50%) know the importance of healthy and clean living behavior during Car Free Days. From all the descriptions of the discussion it can be concluded that in this study the causes and behavior of healthy and clean living were influenced by several factors, namely gender, age, and community knowledge. The community has quite good knowledge about healthy living, but not all people apply healthy behavior in their daily lives. Such as irregular eating patterns, lack of exercise and poor sleep patterns.